Key economic and politico-institutional elements of modern interventionism - Karagiannis, Nikolas (2001)
Discusses important features of the desirable modern state intervention. Deals with the era of change and considers the changing role of government. Examines an institutional system which appears to have been used with enormous success - the Developmental State : the state which takes on a central developmental role in the economy without directly owning most of the productive assests. Pursues aspects of the developmental state model and deals with key elements of the desirable modern state and its new role.